Palaeoenvironments of the last Neanderthals in SW Europe (MIS 3): Cova del Coll Verdaguer (Barcelona, NE of Iberian Peninsula) - Daura, Joan (2017)
Marine isotope stage 3 (MIS 3) was characterised by marked oscillations of extreme cold episodes with very short warm events during the stadial, and several regional differences have been recorded in the ice cores and marine deposits. The aim of this study is to reconstruct this period by evaluating both terrestrial and regional responses. Cova del Coll Verdaguer, a site located on the Iberian Peninsula, preserves a sedimentary deposit dated to between 34 and 56 ka BP and provides an opportunity for evaluating the impact of climate changes on the regional landmass during a period that coincided with the last Neanderthal population on the Iberian Peninsula. Several dating methods, including U-series, electron spin resonance, amino acid racemization and radiocarbon (14C), were applied to the site and the ages obtained show good agreement. The biotic evidence obtained is substantial, comprising floristic data from palynology and charcoal analysis, and faunal data from large and small mammals, birds and gastropods. Environmental reconstruction points to an initially open meadow landscape at the base of the sequence (~56 ka) that progressively changes to a woodland environment dominated by conifers (~34 ka). The presence of few thermophilous taxa, in contrast with lower latitudes of the Iberian Peninsula, is also detected. The environmental conditions of mid-altitude, Mediterranean, limestone mountains for the last Neanderthal populations appear to have been dominated by a forested landscape comprising boreal or mixed coniferous forest, characterised by a low usable biomass with poor comestible plant resources and dispersed herbivore populations.